Cavernous haemangioma of right nasal cavity: a case report - Roslle, Nabihah; Khalid, Mohamad Azizul Fitri; Paiman, Noorasmaliza M.; Hamizan, Aneeza Khairiyah Wan (International Surgery Journal, 2022)
Hemangiomas are common, benign tumors which arise from the proliferation of endothelial cells surrounding blood-filled cavities. Cavernous hemangioma of the nasal cavity is a rare clinical entity but it should be considered in the differential diagnosis of the nasopharyngeal mass and in cases with epistaxis. This lesion is usually found on the lateral wall of nasal cavity and are more common in elderly with no sex preponderance. We present a case of cavernous hemangioma arising from the sphenopalatine area in a 54-year-old female. The tumour was successfully excised by trans-nasal endoscopic approach with pre-operative surgical embolization.